2013
DOI: 10.1111/1744-9987.12145
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Amino Acids Into Dialysate During Hemodialysis Using Hydrophilic and Nonhydrophilic Polyester–Polymer Alloy and Polyacrylonitrile Membrane Dialyzers

Abstract: During hemodialysis, amino acid loss through the dialysate remained a significant problem and was not clear in some dialyzers; therefore, we investigated amino acid loss with hydrophilic and nonhydrophilic polyester-polymer alloy membranes and polyacrylonitrile membranes. Nine maintenance hemodialysis patients were studied to assess amino acid loss during hemodialysis with the three membranes. Total amino acid losses were 85.7 ± 27.2 mg/L, 83.3 ± 16.1 mg/L, and 72.1 ± 22.5 mg/L with the hydrophilic, nonhydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…Malnutrition in HD patients can be caused by combinations of multiple related factors, such as insufficient nutrient intake and metabolic acidosis (16). In addition, as we previously reported, loss of AAs, including CySS, through dialysate inevitably occurs during every HD session (12). In spite of these multifactorial influences on the AA profile, CySS levels were able to show an independent significance in predicting mortality, indicating that CySS levels have a critical role in oxidative stress even in the specific AA profiles of HD patients as well as non-HD patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Malnutrition in HD patients can be caused by combinations of multiple related factors, such as insufficient nutrient intake and metabolic acidosis (16). In addition, as we previously reported, loss of AAs, including CySS, through dialysate inevitably occurs during every HD session (12). In spite of these multifactorial influences on the AA profile, CySS levels were able to show an independent significance in predicting mortality, indicating that CySS levels have a critical role in oxidative stress even in the specific AA profiles of HD patients as well as non-HD patients.…”
Section: Discussionmentioning
confidence: 98%
“…Pre‐dialysis fasting blood samples were collected to examine the amino acids (AA) in the blood from arterial blood lines at the beginning of a week. We measured plasma AA and CySS levels as previously reported . HD‐associated hypotension was defined as a decrease in the systolic blood pressure by 20 mm Hg or a decrease in the mean arterial pressure (MAP) by 10 mm Hg associated with symptoms that include abdominal discomfort, yawning, sighing, nausea, vomiting, muscle cramps, restlessness, dizziness or fainting, and anxiety.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unter Einsatz einer "Sustained low efficiency dialysis (SLED)" liegt der Verlust an Aminosäuren laut einer Untersuchung in derselben Größenordnung wie bei kontinuierlichen Nierenersatzverfahren [148]. In Abhängigkeit von der Art der eingesetzten Filtermembranen kann es jedoch zu einem unterschiedlich hohen Verlust spezifischer Aminosäuren kommen [149].…”
Section: Proteinzufuhr Unter Mechanischer Nierenersatztherapieunclassified
“…During HD, both metabolic waste products as well as circulating amino acids are able to diffuse through the semipermeable dialysis membrane [11]. The diffusion into the dialysate results in a considerable extraction of circulating amino acids throughout HD [30,[53][54][55][56]. We have recently shown that during a single HD session,~12 g amino acids are extracted from the circulation in CHD patients who ingest their habitual diet during HD [57].…”
Section: Dietary Protein Intake In Esrd Patients On Hdmentioning
confidence: 99%